Molecular characterization of a porcine teschovirus HuN-1 isolate proliferating in PK-15 cell - Molin Chen; Wei Tang; Xiuguo Hua (BMC Veterinary Research, 2018)
Abstract Background Porcine teschoviruses (PTVs) are small non-enveloped viruses with single-stranded, positive sense genomic RNA, belonging to the family Picornaviridae. Natural infections of teschoviruses are limited to pigs. Results In this study, a PTV HuN-1 was found that it could be proliferated in PK-15 cell, and it came from the pig fecal samples from Hunan province, in central China. The complete genome of the HuN-1 was amplified by RT-PCR and sequenced. The complete genome of HuN-1 isolate is 7098 nt, which shares the highest sequence identity (85.9%) with the PTV 8 strain of Jilin/2003/2 and Fuyu/2009/2. The HuN-1 isolate contains only one ORF (from 320 to 7039 nt) coding a 2240 amino acid polyprotein. Aligned sequences show that more mutations occurred in the structural region than in the nonstructural region. Phylogenetic analysis showed that HuN-1 isolate did not clustered with the hitherto reported strains, according to P1 sequences, forming a subgroup in the PTV cluster. Conclusion In this study, complete genome of PTV HuN-1 was cloned and sequenced. Detection and characterization of further PTV strains from different geographic areas are important to understand the worldwide distribution and heterogeneity (serotype) of PTVs and their association with symptomatic infections in pigs.